656. E. coli Clone Sharing and Persistence Within Households (HHs) in Relation to Fluoroquinolone (FQ) Resistance and ST131 Status. (26th November 2018) - Boettcher, Jessica; Clabots, Connie; Porter, Stephen B; Johnson, James R
Abstract: Background: Extraintestinal E. coli infections, a perennial source of morbidity and mortality, are increasingly difficult to treat due to emerging antibiotic resistance. Within-HH sharing of E. coli strains may contribute to this problem, but is poorly understood. Accordingly, we assessed E. coli strain sharing within the HHs of veterans with a clinical E. coli isolate, including in relation to FQ resistance and ST131 status. Methods: Twenty-two veterans with a clinical E. coli isolate (11 FQ-resistant [FQ-R], 11 FQ-susceptible [FQ-S]) and their HH members underwent serial stool sampling (2–6 occasions each). Stool samples were cultured selectively for FQ-S and FQ-R E. coli . Per sample, 10 E. coli colonies underwent PCR-based profiling; one colony per profile underwent pulsotyping and PCR-based ST131 detection, as did all clinical isolates. Each strain's extent of within-HH sharing and colonization were calculated. Results: Of the 11 FQ-R clinical isolates, seven were ST131 and four non-ST131; all FQ-S clinical isolates were non-ST131. The 22 HHs included 68 total subjects (49 humans, 19 pets), with a per-HH mean of three subjects, 9.5 total fecal samples, and 6.7 unique strains. The index patient's stool yielded the corresponding clinical strain in 91% of FQ-R HHs, but only 45% of FQ-S HHs. Sharing of the clinical strain occurred in 45% of FQ-R HHs (43% if ST131, 50% if non-ST131), vs. 27% of FQ-S HHs. For the 22 clinical strains, the extent of within-HH sharing and colonization was greater for FQ-R than FQ-S strains (sharing index, 0.45 vs. 0.15; colonization index, 0.47 vs. 0.14). The FQ-R HHs also yielded 12 additional (non-clinical) FQ-R strains, the FQ-S HHs only 1. Non-clinical FQ-R strains colonized much less extensively than FQ-R clinical strains and were not shared between HH members. Conclusion: Compared with FQ-S clinical E. coli, FQ-R clinical E. coli more frequently colonize the index patient, are shared among HH members, and co-occur with other HH FQ-R strains, all of which may drive population-level resistance. Given the potentially important clinical implications of within-HH strain sharing and colonization, better understandings are needed of its mechanisms, including characteristics of the strain, host, and gut microbiota. Disclosures: J. R. Johnson, Crucell/Janssen: Consultant, Consulting fee. Allergan: Grant Investigator, Research support. Merck: Grant Investigator, Research support. Melinta: Grant Investigator, Research support. Tetraphase: Grant Investigator, Research support. Syntiron: Consultant, Consulting fee.